2021
DOI: 10.1155/2021/9648579
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen Kinetics Effects on Outcomes of Low-Volume Metastatic Prostate Cancer Patients Receiving Androgen Deprivation Therapy

Abstract: Background. The present study aimed to analyse factors influencing the effects of androgen deprivation therapy (ADT) in patients with newly diagnosed metastatic castration-naïve prostate cancer (mCNPC), especially in low-volume disease (LVD), according to subclassification of metastatic prostate cancer established by the CHAARTED trial. Materials and Methods. We reviewed 648 patients with newly diagnosed mCNPC receiving ADT at Chang Gung Memorial Hospital from January 2007 to December 2016. Basic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…We investigated the prognostic significance of the slope associated with nadir PSA in patients treated with PADT. In accordance with previous reports, 12 , 15 , 17 our results also showed that nPSA‐DS, nPSA‐LS, and nPSA‐PDS were associated with PFS and OS in the univariate analysis. Moreover, we found that nadir PSA and nPSA‐DS following PADT were independently associated with PFS and OS, even after adjusting for other factors.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We investigated the prognostic significance of the slope associated with nadir PSA in patients treated with PADT. In accordance with previous reports, 12 , 15 , 17 our results also showed that nPSA‐DS, nPSA‐LS, and nPSA‐PDS were associated with PFS and OS in the univariate analysis. Moreover, we found that nadir PSA and nPSA‐DS following PADT were independently associated with PFS and OS, even after adjusting for other factors.…”
Section: Discussionsupporting
confidence: 93%
“…Akbay et al 15 used a formula for assessing the PSA decline pattern to calculate the declining slope to nadir PSA (ds‐nPSA), and they found that patients with ds‐nPSA> − 0.507 had prolonged PFS in the univariate analysis. Lin et al 17 calculated the PSA reduction rate (PSARR) according to the formula PSARR = (100* (iPSA‐nPSA/iPSA)/TTPN). In the univariate analysis, the PSARR was a statistically significant indicator for disease progression and OS, but no statistical significance was found in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRC is the second most commonly diagnosed cancer in men worldwide [ 78 ]. For patients with metastatic PRC, androgen deprivation therapy (ADT) has been the gold standard [ 79 ]. Androgens control the proliferation and survival of prostate epithelial cells by binding to the AR, which is also involved in the development of PRC and regulates specific target genes [ 80 , 81 ].…”
Section: The Regulatory Roles Of Tm4sf1 In Different Cancer Typesmentioning
confidence: 99%